Serological Survey and Factors Associated with Toxoplasma gondii Infection in Domestic Goats in Myanmar - Saw Bawm; Wint Yi Maung; Myat Yee Win; May June Thu; Hla Myet Chel; Tin Aye Khaing; Soe Soe Wai; Lat Lat Htun; Tin Tin Myaing; Saruda Tiwananthagorn; Makoto Igarashi; Ken Katakura (Scientifica)
Goat farming is important for the livelihood of millions of rural people because it contributes to food security and creation of assets. However, infection of goats with Toxoplasma gondii could be a source of parasite transmission to humans. The information on T. gondii infection of goat was not reported yet in Myanmar. A total of 119 goat serum samples were collected from three cities in the central region of Myanmar for T. gondii antibody survey. With the occurrence value obtained in this first study, a second one, more complete, with larger number (162) of animals and properties, was carried out and the risk factors and prevalence were determined. In both studies the samples were analyzed by the LAT. Of these, 32 (11.4%) samples were showed to be positive. The infection was associated with the presence of cats at the farm (odds ratio [OR] = 4.66, 95% confidential interval [CI] = 1.03–21.06), farming with different animal species (sheep, cattle, and pigs) (OR = 4.33, 95% CI = 1.57–11.94), and farming without good management practices (OR = 0.23, 95% CI = 0.06–0.83). This is the first T. gondii prevalence study in goats in the country.